Spectral Variability of the Symbiotic Star CH Cyg - Mikailov Khidir Mustafa; Mammadov Ruslan Tavakkul; Rustamov Bayram Nizam; Rustamova Aysel Bayram (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
On July 15, 2015, the second telescope of the Shamakhi Astrophysical Observatory (ShAO) was used to collect 14 echelle spectra of the symbiotic star CH Cyg over the course of six hours of nocturnal exposures. Along the profiles of the lines Нα and Нβ, the intensity of line Hel λ5876 Å fluctuates simultaneously with variations in the intensity ratios of the blue and red emission components. The Hel λ5876 Å line’s center intensities and corresponding widths correlate with information from the blue emission component of the lines. There are certain correlations between the radial velocities of the absorption DNaI and the emission line Нα.